The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3390/jcm12062442
|View full text |Cite
|
Sign up to set email alerts
|

Cryoballoon-Induced Circumferential Pulmonary Vein Fibrosis, Assessed by Late Gadolinium-Enhancement Cardiac Magnetic Resonance Imaging, and Its Correlation with Clinical Atrial Fibrillation Recurrence

Abstract: Background: Prior studies evaluating post-atrial fibrillation (AF) ablation pulmonary vein (PV) ostial gaps via magnetic resonance imaging (MRI) have shown circumferential PV fibrosis in a minority of patients, and their correlation with AF recurrence was weak. These studies were mostly based on radio-frequency AF ablations. Aim: We aimed to assess cryoballoon ablation-induced PV fibrosis via MRI and its correlation with AF recurrence. Methods and Results: This was a prospective study of consecutive patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
(87 reference statements)
1
2
0
Order By: Relevance
“…A complete circumferential fibrosis in all of the PVs was found in a minority of treated patients, and a clear relationship between circumferential fibrosis and long-term procedure success did not always emerge [ 19 , 20 , 21 , 22 ]. Similar results were obtained in studies on cryoballoon ablation [ 23 , 24 , 25 , 26 ]. Moreover, dense scarring and interstitial fibrosis can be difficult to differentiate via MRI, potentially leading to inaccurate estimations of lesion gaps at the PV ostium.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…A complete circumferential fibrosis in all of the PVs was found in a minority of treated patients, and a clear relationship between circumferential fibrosis and long-term procedure success did not always emerge [ 19 , 20 , 21 , 22 ]. Similar results were obtained in studies on cryoballoon ablation [ 23 , 24 , 25 , 26 ]. Moreover, dense scarring and interstitial fibrosis can be difficult to differentiate via MRI, potentially leading to inaccurate estimations of lesion gaps at the PV ostium.…”
Section: Discussionsupporting
confidence: 88%
“…Moreover, dense scarring and interstitial fibrosis can be difficult to differentiate via MRI, potentially leading to inaccurate estimations of lesion gaps at the PV ostium. A recent analysis on 19 patients undergoing cryoballoon ablation found that the absence of a major gap in any PV was associated with freedom from AF recurrence at 12 months [ 26 ]. However, in this experience, a qualitative rather than a quantitative definition of circumferential lesion was adopted, allowing for a gap of up to one-third of the PV ostium for the definition of complete PV fibrosis; moreover, a significant percentage of patients with major gaps were nonetheless free from arrhythmia recurrences.…”
Section: Discussionmentioning
confidence: 99%
“…Tovia-Brodie and coworkers 135 reported the anatomical accuracy of the KODEX-EPD (Philips, Netherlands) novel 3D mapping system of the left atrium during pulmonary vein isolation and its excellent correlation with computer tomography imaging. In the second paper, Rav Acha and colleagues 136 showed that cryoballoon AF ablation results in circumferential pulmonary vein fibrosis in the majority of pulmonary veins, as assessed by a new clinically relevant magnetic resonance imaging (MRI) analysis. A significant correlation was found between major pulmonary veins gaps on postablation MRI and AF recurrence, suggesting that MRI might have the ability to predict AF recurrence.…”
Section: Afl/af Ablationmentioning
confidence: 99%